Evolution of the rice blast pathogen on spatially structured rice landraces maintains multiple generalist fungal lineages - Sajid Ali; Pierre Gladieux; Sebastien Ravel; Henri Adreit; Isabelle Meusnier; Joelle Milazzo; Sandrine Cros‐Arteil; François Bonnot; Baihui Jin; Thomas Dumartinet; Florian Charriat; Alexandre Lassagne; et al. (Molecular Ecology, 2023)
Traditional agrosystems, where humans, crops and microbes have coevolved over long periods, can serve as models to understand the ecoevolutionary determinants of disease dynamics and help the engineering of durably resistant agrosystems. Here, we investigated the genetic and phenotypic relationship between rice ( Oryza sativa ) landraces and their rice blast pathogen ( Pyricularia oryzae ) in the traditional Yuanyang terraces of flooded rice paddies in China, where rice landraces have been grown and bred over centuries without significant disease outbreaks. Analyses of genetic subdivision revealed that indica rice plants clustered according to landrace names. Three new diverse lineages of rice blast specific to the Yuanyang terraces coexisted with lineages previously detected at the worldwide scale. Population subdivision in the pathogen population did not mirror pattern of population subdivision in the host. Measuring the pathogenicity of rice blast isolates on landraces revealed generalist life history traits. Our results suggest that the implementation of disease control strategies based on the emergence or maintenance of a generalist lifestyle in pathogens may sustainably reduce the burden of disease in crops.

Functional diversity of leaf nitrogen concentrations drives grassland carbon fluxes - Alexandru Milcu; Christiane Roscher; Arthur Gessler; Dörte Bachmann; Annette Gockele; Markus Guderle; Damien Landais; Clément Piel; Christophe Escape; Sebastien Devidal; Olivier Ravel; Nina Buchmann; et al. (Ecology Letters, 2014)
Little is known about the role of plant functional diversity for ecosystem‐level carbon (C) fluxes. To fill this knowledge gap, we translocated monoliths hosting communities with four and 16 sown species from a long‐term grassland biodiversity experiment (‘The Jena Experiment’) into a controlled environment facility for ecosystem research (Ecotron). This allowed quantifying the effects of plant diversity on ecosystem C fluxes as well as three parameters of C uptake efficiency (water and nitrogen use efficiencies and apparent quantum yield). By combining data on ecosystem C fluxes with vegetation structure and functional trait‐based predictors, we found that increasing plant species and functional diversity led to higher gross and net ecosystem C uptake rates. Path analyses and light response curves unravelled the diversity of leaf nitrogen concentration in the canopy as a key functional predictor of C fluxes, either directly or indirectly via LAI and aboveground biomass.